2008
DOI: 10.1248/bpb.31.890
|View full text |Cite
|
Sign up to set email alerts
|

<small>L</small>-Arginine Protects from Pringle Manoeuvere of Ischemia-Reperfusion Induced Liver Injury

Abstract: During hepatic resection, the risk of severe intra-operative bleeding is a major risk.1) To prevent massive blood loss, continuous or intermittent vascular clamping of the hepatic artery and portal vein ligation is known as "Pringle manoeuvere" is an efficient method to reduce hemorrhage. 2,3) "Pringle manoeuvere" is a technique which leads to ischemic and reperfusion injury. Ischemia and reperfusion results in complex metabolic, 4) immunological 5) and micro vascular 6) changes, which together may contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 21 publications
0
17
1
Order By: Relevance
“…In contrast to our results, Chattopadhyay et al [6] demonstrated that pre-treatment with L-arginine significantly decreased serum-ALAT after 1 h ischemia followed by 3 h reperfusion. Histopatology study showed markedly diminished hepatocellular injury in L-arginine pretreated rats during the hepatic I/R, which correlated with decreased plasma ALAT.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our results, Chattopadhyay et al [6] demonstrated that pre-treatment with L-arginine significantly decreased serum-ALAT after 1 h ischemia followed by 3 h reperfusion. Histopatology study showed markedly diminished hepatocellular injury in L-arginine pretreated rats during the hepatic I/R, which correlated with decreased plasma ALAT.…”
Section: Discussioncontrasting
confidence: 99%
“…Shimamura et al 23 observed a significant increase and maximum of AST levels after 12 hours of reperfusion in a model of hepatic IR, with return to basal level from the 3 rd day of reperfusion. Other authors also evidenced a significant increase in aminotransferases levels after hepatic IR 22,24,25 .…”
Section: Discussionmentioning
confidence: 82%
“…Hepatic ischemia was created by occluding all structures (hepatic artery, portal vein, and bile duct) leading to the left and median liver lobes (~70% of liver mass) with an atraumatic microvascular clamp for 45 min followed by 2 h reperfusion [5]. The body temperature was monitored and maintained at 37 ± 0.4°C by a heating lamp and warm sterile moistened gauze placed over the laparotomy to avoid dehydration.…”
Section: Hepatic Ischemia-reperfusionmentioning
confidence: 99%